A micro-tensile testing chip–integrated piezoresistive cells for tension measurement and axial alignment. (June 2014) - Zhang, Duanqin; Yang, Faliang; Chu, Jinkui
Mechanical testing of micro/nano-materials is very important for design, performance realization, and reliability analysis of micro/nano-electromechanical systems. Mechanical characterization of micro/nano-materials is rather difficult in the handling and alignment of the specimens, measurement of the displacement, and the load for both the off-chip testing method and the integrated on-chip testing method. In this article, a micro-tensile testing chip–integrated piezoresistive cells and a specimen are developed to solve the problems of tension measurement and axial alignment. Based on the piezoresistive effect, the configuration of the chip, especially the parts of the cantilevers, which carry the piezoresistive cells and the cells, is designed, and the tensile force and non-axis alignment error can be measured simultaneously. The chip is prepared with bulk micromachining of silicon. The performance of the chip is calibrated using an off-chip actuated micro-tensile tester, and the sensitivity coefficient of the piezoresistive cells is equal to 0.017 mV/mN.